FLUKS CO2 MALAM HARI PADA PERKEBUNAN KELAPA SAWIT DI LAHAN GAMBUT - Ahmad Subuh; Evi Gusmayanti; Muhammad Pramulya (Perkebunan dan Lahan Tropika, 2019)
The use of peat land for the development of oil palm plantations is considered to have a negative impact on the environment based on the release of CO2 emissions. Some of the results of the study show that emissions measurements using a closed hood method with a measurement duration of 2-4 minutes that takes place during the day. The aim of this study was to measure CO2 flux at night on oil palm plantation areas of 9 years and 10 years in peatlands and to analyze the relationship of CO2 flux at night in oil palm plantations on peat with Temperature Soil, Groundwater Face, Water Content Gravimetric, Soil pH, and Eh Soil. Location this research was carried out on the oil palm plantation area of PT. Sintang Raya. The location of the research plot is located in the village of Olak-olak Kubu, Kubu District, Kubu Raya Regency, West Kalimantan in July 2018 until October 2018. Measurements were made using vaisala with CO2 sensors namely InfraRed Gas Analyzer (vaisala) and conducted for ≤4 minutes per plot. This measurement is carried out in the afternoon until the morning and is repeated every 4 hours at 18.00, 22.00, 02.00 and 06.00. The measurement of CO2 flux is done once a week starting from August to September. The results showed that nighttime CO2 flux in oil palm plants on peatland was between 0.27 g CO2 m-2 hours-1 to 0.34 g CO2 m-2 hours-1 or equivalent to 26.86 tons CO2 ha-1 year-1 to 29.74 tons CO2 ha-1 year-1. Differences in levels of organic matterand ash content between peatlands in TM 6 and TM 7 did not cause significant differences in CO2 flux values between the two locations. Variation in the time of measurement of real estate at night, but does not affect real changes in flux values. This is related to the level of organic matter, ash content, and also the temperature associated with CO2 flux, including other factors that also determine the amount of nighttime CO2 flux on peatland.Keywords: CO2 Flux, Measurement Time, Plant Age.